The Relationship Between Topography, Bedrock Weathering, and Water Storage Across a Sequence of Ridges and Valleys. Issue 4 (28th April 2021) - Pedrazas, Michelle A.; Hahm, W. Jesse; Huang, Mong‐Han; Dralle, David; Nelson, Mariel D.; Breunig, Rachel E.; Fauria, Kristen E.; Bryk, Alexander B.; Dietrich, William E.; Rempe, Daniella M.
Abstract: Bedrock weathering regulates nutrient mobilization, water storage, and soil production. Relative to the mobile soil layer, little is known about the relationship between topography and bedrock weathering. Here, we identify a common pattern of weathering and water storage across a sequence of three ridges and valleys in the sedimentary Great Valley Sequence in Northern California that share a tectonic and climate history. Deep drilling, downhole logging, and characterization of chemistry and porosity reveal two weathering fronts. The shallower front is ∼7 m deep at the ridge of all three hillslopes, and marks the extent of pervasive fracturing and oxidation of pyrite and organic carbon. A deeper weathering front marks the extent of open fractures and discoloration. This front is 11 m deep under two ridges of similar ridge‐valley spacing, but 17.5 m deep under a ridge with nearly twice the ridge‐valley spacing. Hence, at ridge tops, the fraction of the hillslope relief that is weathered scales with hillslope length. In all three hillslopes, below this second weathering front, closed fractures and unweathered bedrock extend about one‐half the hilltop elevation above the adjacent channels. Neutron probe surveys reveal that seasonally dynamic moisture is stored to approximately the same depth as the shallow weathering front. Under the channels that bound our study hillslopes, the two weathering fronts coincide and occur within centimeters of the ground surface. Our findings provide evidence for feedbacks between erosion and weathering in mountainous landscapes that result in systematic subsurface structuring and water routing. Plain Language Summary: The patterns of bedrock weathering concealed beneath the surface have important implications for the water cycle. In many upland landscapes, sequences of ridges and valleys result from river incision into bedrock, which organizes the landscape into hillslopes separated by channels. While surface topography of these landscapes is easily visible, the structure of weathered bedrock beneath the surface and its relationship to overlying topography are unknown. In this study, we observed systematic patterns of weathering and water storage under three hillslopes that make up a repeating ridge‐valley sequence formed in sedimentary bedrock. Across the study area, weathering is thickest under ridges and thins downslope toward adjacent valleys, where fresh bedrock lies almost directly below channels. Interestingly, the depth of extensive weathering and seasonal water storage at the ridges was comparable across all three hillslopes, while open fractures and discoloration persist to a deeper depth under the longer hillslope. These observations provide a basis for scaling point measurements of weathering to the landscape scale, which is a much‐needed tool for models of earth surface processes. Key Points: Bedrock weathering and water storage patterns are similar across a sequence of ridges and valleys Discrete fracturing and discoloration extend deeper into the hillslope relative to pyrite and organic carbon oxidation The relief of weathering fronts above local channels scales with hillslope length